Locomotor Performance During Rehabilitation of People With Lower Limb Amputation and Prosthetic Nonuse 12 Months After Discharge - Roffman, C.; Buchanan, J.; Allison, Garry (2015)
Background: It is recognized that multifactorial assessments are needed to evaluate balance and locomotor function in people with lower limb amputation. There is no consensus on whether a single screening tool could be used to identify future issues with locomotion or prosthetic use. Objective: The purpose of this study was to determine whether different tests of locomotor performance during rehabilitation were associated with significantly greater risk of prosthetic abandonment at 12 months postdischarge. Design: This was a retrospective cohort study. Method: Data for descriptive variables and locomotor tests (ie, 10-Meter Walk Test [10MWT], Timed “Up & Go” Test [TUGT], Six-Minute Walk Test [6MWT], and Four Square Step Test [FSST]) were abstracted from the medical records of 201 consecutive participants with lower limb amputation. Participants were interviewed and classified as prosthetic users or nonusers at 12 months postdischarge. The Mann-Whitney U test was used to analyze whether there were differences in locomotor performance. Receiver operating characteristic curves were generated to determine performance thresholds, and relative risk (RR) was calculated for nonuse. Results: At 12 months postdischarge, 18% (n=36) of the participants had become prosthetic nonusers. Performance thresholds, area under the curve (AUC), and RR of nonuse (95% confidence intervals [CI]) were: for the 10MWT, if walking speed was ≤0.44 ms−1 (AUC=0.743), RR of nonuse=2.76 (95% CI=1.83, 3.79; P<.0001); for the TUGT, if time was ≥21.4 seconds (AUC=0.796), RR of nonuse=3.17 (95% CI=2.17, 4.14; P<.0001); for the 6MWT, if distance was ≤191 m (AUC=0.788), RR of nonuse=2.84, (95% CI=2.05, 3.48; P<.0001); and for the FSST, if time was ≥36.6 seconds (AUC=0.762), RR of nonuse=2.76 (95% CI=1.99, 3.39; P<.0001).LIMITATIONS: Missing data, potential recall bias and assessment times varied. CONCLUSIONS: Locomotor performance during rehabilitation may predict future risk of prosthetic non-use. It may be implied that the 10MWT has the greatest clinical utility as a single screening tool for prosthetic non-use given the highest proportion of participants were able to perform this test early in rehabilitation. However as locomotor skills improve other tests in particular the 6MWT have specific clinical utility. To fully enable implementation of these locomotor criteria for prosthetic non-use into clinical practice, validation is warranted.